2010
DOI: 10.1016/j.jdent.2010.05.005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ability of a laser fluorescence device in quantifying approximal caries lesions in primary molars

Abstract: LFpen readings present low correlation with approximal caries lesion depth and low reproducibility, especially in white-spot lesions. Therefore, the device could not be a suitable method for monitoring non-cavitated approximal caries lesion in primary molars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 14 publications
1
23
1
1
Order By: Relevance
“…5 However whilst current research in the field of cardiology has highlighted innovative minimally invasive techniques using laser fluorescence. 31,32 Disappointingly, these initial studies recorded low correlation with approximal caries depth as assessed by radiography especially within the early lesion. In addition a previous systematic review 33 confirmed these findings and stressing the need of future research in this field.…”
Section: Discussionmentioning
confidence: 99%
“…5 However whilst current research in the field of cardiology has highlighted innovative minimally invasive techniques using laser fluorescence. 31,32 Disappointingly, these initial studies recorded low correlation with approximal caries depth as assessed by radiography especially within the early lesion. In addition a previous systematic review 33 confirmed these findings and stressing the need of future research in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports have been published concerning the performance of different methods in detecting proximal caries lesions in the primary teeth, 3,[6][7][8]14 the influence of interdental spacing on the performance of these methods has not yet been studied. Moreover, associated factors related to the efficacy of temporary separation in the primary teeth require further studies to evaluate the benefits of this method.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…5 Since closed proximal spaces in the primary teeth are strongly correlated with caries occurrence, different methods of caries detection have been studied. 3,6,7 Contact points hamper direct visual inspection of…”
Section: Introductionmentioning
confidence: 99%
“…17 LF devices are based on the capture, analysis, and quantification of fluorescence emitted from bacterial porphyrins and other chromophores when the tooth surface is illuminated by a diode laser at a 655 nm wavelength. The LFpen has shown good accuracy and reproducibility in detecting approximal caries, and it has shown promising results in vitro on permanent 18 and primary teeth 19 and in vivo on permanent 20 and primary teeth. 2 Recently, an LED-based device was developed (Midwest Caries I.D.…”
Section: Introductionmentioning
confidence: 99%